ISLAMIC FINTECH'S ROLE IN SUSTAINABLE FINANCE: EMPOWERING WOMEN IN ACEH - Khairisma; Mukhlish Muhammad Nur; Mardiaton; Muhammad Fazlurrahman Syarif; Muhammad Mirza Amanda; Rini Rosita (RADJA PUBLIKA, 2024)
This research examines the influence of Islamic Fintech as inclusive finance on sustainable finance in the Aceh province, with women’s empowerment as a moderating variable. The research approach used is quantitative, utilizing multiple regression analysis (MRA) for the linear regression model. The research methodology involves several steps, including data observation, identifying key issues, setting research objectives, literature review, data collection, data processing, results analysis, and research evaluation. The study aims to investigate the extent to which the existence of Islamic Fintech contributes to sustainable financial development in Aceh. Additionally, the research focuses on women's empowerment as a moderating variable, specifically its impact on the relationship between Islamic Fintech and sustainable finance. By employing a quantitative approach, this study seeks to generate empirical evidence that can provide an in-depth understanding of the influence of Islamic Fintech on sustainable finance and to evaluate whether women’s empowerment can moderate this relationship. The research findings show that Islamic Fintech significantly impacts sustainable finance, while women’s empowerment does not moderate the relationship between Islamic Fintech and sustainable finance.